Makna Pendidikan Multikultural bagi Siswa - Marlina, Murni Eva (Universitas Negeri Medan, 2014)
Indonesia is a multicultural and developing country. Yet nowadays many social problems are taking place in various fields of life. By comparing with the other multicultural country in the ASEAN region, it is still being left behind by Singapore and Thailand. As the November 1997 monatary crises, so that implied to another sectors. Consequently, cultural capital as collective power of community such as togetherness, solidarity, cooperation, tolerance, trust, and responsibility which are hold by each community members, have been weakening even nearly broken. Such dynamic and developing society like Indonesia very need attention. As national and local leader, the experts in social and educational matter obligated to serve as agent of social change for the society. Th plural condition of Indonesian society such as ethnic, race, religion, and social status to contibute on development of society. Therefore, containing multicultural matter to education system is very important, either as substance or model of learning due to could contribute in debriefing, developing insight and personality of students. Beside it practices students in facing social problem in middle of their community.